Urinary 5-hydroxymethyluracil and 8-oxo-7, 8-dihydroguanine as potential biomarkers in patients with colorectal cancer. (July 2015) - Rozalski, Rafal; Gackowski, Daniel; Siomek-Gorecka, Agnieszka; Starczak, Marta; Modrzejewska, Martyna; Banaszkiewicz, Zbigniew; Olinski, Ryszard
Abstract Context: Oxidative stress linked with chronic inflammation is associated with etiology of the colorectal cancer. Objectives: To assess the diagnostic utility of urinary excretion of oxidatively modified DNA bases/nucleoside: 8-oxo-7, 8-dihydroguanine (8-oxoGua), 8-oxo-7, 8-dihydro-2′-deoxyguanosine (8-oxodGuo) and 5-hydroxymethyluracil (5-hmUra). Materials and methods: Seventy-two healthy controls, 15 patients with adenomas and 56 colorectal cancer patients were recruited. Results: The receiver operating characteristic (ROC) curve analysis showed that the area under the curve (AUC) for all markers tested separately was <0.7. The combination of these modifications showed better diagnostic power (AUC = 0.778 for 8-oxoGua + 8-oxodG)/5hmUra ratio). Conclusion: Urinary DNA modifications may reflect the oxidative stress/chronic inflammation in colorectal cancer but diagnostic performance for early-detection is moderate.